2022
DOI: 10.37934/araset.29.1.177187
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Energy Consumption and Industrial Output-Based on GMM Model of Dynamic Panel Data in China

Abstract: At present, China is in the historical intersection period of the "two centenary" goals. The realization of the "carbon neutral" goal has brought new opportunities for the development of China's energy sector. Based on the GMM estimation method of the dynamic panel model, this paper studies the relationship between energy consumption and industrial output by using China's provincial data from the years 2008 to 2018. The results show that the impact of coal consumption on industrial output tends to be declining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(23 reference statements)
0
0
0
Order By: Relevance
“…This situation has shown that a comprehensive and accurate assessment of the power transformer in operation is crucial for the operation of the plant, and that a failure of this strategic unit will result in a significant loss of revenue. In general, production efficiency is very important, with power interruptions being a serious problem that can lead to losses, as reported in [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…This situation has shown that a comprehensive and accurate assessment of the power transformer in operation is crucial for the operation of the plant, and that a failure of this strategic unit will result in a significant loss of revenue. In general, production efficiency is very important, with power interruptions being a serious problem that can lead to losses, as reported in [2][3][4].…”
Section: Introductionmentioning
confidence: 99%